Induction of apoptosis by piperine in human cervical adenocarcinoma via ROS mediated mitochondrial pathway and caspase-3 activation - Jafri, Asif; Siddiqui, Sahabjada; Rais, Juhi; Ahmad, Md Sultan; Kumar, Sudhir; Jafar, Tabrez; Afzal, Mohammad; Arshad, Md (Technische Universität Dortmund, 2019)
Piperine (1-piperoylpeperdine), a nitrogenous pungent substance, is present in the fruits of black pepper (Piper nigrum Linn.) and long pepper (Piper longum Linn.). It possesses several pharmacological properties and has been extensively explored for its anti-cancerous activities. The mechanism underlying its anti-cancer potential in human cervical adenocarcinoma (HeLa) cells is not well interpreted. The anti-proliferative effect and the mode of action of piperine were investigated through some potent markers of apoptosis viz.reactive oxygen species (ROS) generation, cellular apoptosis and loss of mitochondrial membrane potential (MMP). DNA fragmentation, cell cycle kinetics, caspase-3 activity and cell migration assays were also conducted to observe the efficacy of piperine against HeLa cells. The results showed that piperine exposure induces apoptosis significantly in a dosedependent manner and inhibits the growth of HeLa cells with an increase in ROS generation, nuclear condensation and delayed wound healing. In addition, piperine also encourages cell death by the loss of MMP, DNA fragmentation and the activation of caspase-3. Growth inhibition of HeLa cells was found to be associated with G2/M phase arrest and sub-G1 accumulation. The present study provides useful insight into the apoptotic potential of piperine and further in vivo and clinical studies will be needed for its validation and in the finding of more effective and least toxic regimens against cervical cancer.
EXCLI Journal;Vol. 18 2019
Keywords: Anti-tumor; Caspase-3; Cell cycle kinetics; Piperine; ROS; 610